Measles vaccine coverage and factors related to uncompleted vaccination among 18-month-old and 36-month-old children in Kyoto, Japan - Okamoto Shigeru; Nakayama Takeo; Matsumura Takayo; Ito Hideko (BMC, 2005)
Abstract Background Due to low vaccine coverage, Japan has not only experienced outbreaks of measles but has also been exporting it overseas. This study aims to survey measles vaccine coverage and the factors uncompleted vaccination among community-living children. Methods Subjects were the parents whose children had undergone either an 18-month or a 36-month checkup publicly provided by Kyoto City during November 2001 to January 2002. An anonymous self-administered questionnaire survey was conducted. Results The coverage was 73.2% among the 18-month-old children (n = 2707) and 88.9% among the 36-month-old children (n = 2340), respectively. The following characteristics of mothers were related to uncompleted measles vaccination: aged below 30, working, concerned about the adverse events of the vaccine, and had insufficient knowledge. Similarly, the following characteristics among children were related to uncompleted measles vaccination: not the first-born child, interacting with other children in group settings. The coverage was the lowest among the children whose mothers were concerned about the adverse events of the vaccine without proper knowledge of measles and its vaccination. Conclusion To increase vaccine coverage among children, parents' awareness about measles and vaccination against it should be promoted, especially for working mothers. Efforts to enhance access to vaccination services and to communicate with parents about changing vaccination schedules are necessary.